Cloridrato de ractopamina em dietas para suínos em terminação - Ferreira, Matheus Soares da Silva (2011)
The present work was carried out to evaluate different inclusion levels of ractopamine in diets for finishing pigs. Fifty animals with initial weight of 74.08 (1.42) kg selected for high meat deposition were used, randomly allotted in five blocks. Each experimental unit had two animals, barrow and gilt, fed diets with ractopamine (0, 5, 10, 15 and 20 ppm) for 28 days. Growth performance and carcass characteristics were evaluated. Ractopamine improved final weight, average daily gain, feed:gain ratio, backfat thickness, loin depth, loin eye area and lean tissue yield, but did not influence feed intake, cut yields and belly quality. No differences were found among the doses of ractopamine utilized. The optimum level of supplementation of this additive, as estimated by the Linear Response Plateau regression model, was between 4.09 and 5.14 ppm. There was an average increase of 6.09% in the bonus index when ractopamine was used. It was concluded that ractopamine is efficient in increasing the performance and carcass characteristics of finishing pigs.